2012
DOI: 10.5424/fs/2112211-12086
|View full text |Cite
|
Sign up to set email alerts
|

Biomass expansion factors for Eucalyptus globulus stands in Portugal

Abstract: One of several procedures for estimating carbon stocks in forests is the estimation of tree or stand biomass based on forest inventory data. The two approaches normally used to convert field measurements of trees to stand biomass values are allometric biomass equations and biomass expansion factors (BEFs). BEFs are used in published National Forest Inventory results in which biomass is not estimated or as a complement of growth models that do not include biomass predictions. In this paper, the effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…The range of R/S of our data, in planted trees (0.15 to 0.65), was very similar to those reported by Cairns et al (1997), for many tropical, temperate boreal species (0.1 to 0.6), and Bernardo et al (1998) (0.2 to 0.6) for several eucalypt species in Brazil. A number of authors have reported decreasing R/S values with tree size or aboveground biomass (Misra et al 1998;Levillain et al 2011;Resh et al 2003;Kuyah et al 2013) or age (Laclau et al 2000;Soares and Tomé 2012) in eucalypt. However, studies modeling the belowground biomass and R/S ratios as a function of dendrometric variables are extremely scarce in eucalypt species (Paul et al 2008;Jonson and Freudenberger 2011), and they show the same trend with diameter than in our study.…”
Section: Belowground Biomass Allometries For Planted and Coppiced Standsmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of R/S of our data, in planted trees (0.15 to 0.65), was very similar to those reported by Cairns et al (1997), for many tropical, temperate boreal species (0.1 to 0.6), and Bernardo et al (1998) (0.2 to 0.6) for several eucalypt species in Brazil. A number of authors have reported decreasing R/S values with tree size or aboveground biomass (Misra et al 1998;Levillain et al 2011;Resh et al 2003;Kuyah et al 2013) or age (Laclau et al 2000;Soares and Tomé 2012) in eucalypt. However, studies modeling the belowground biomass and R/S ratios as a function of dendrometric variables are extremely scarce in eucalypt species (Paul et al 2008;Jonson and Freudenberger 2011), and they show the same trend with diameter than in our study.…”
Section: Belowground Biomass Allometries For Planted and Coppiced Standsmentioning
confidence: 99%
“…A number of studies have recently been developed to estimate E. globulus tree total aboveground biomass and its components (stem wood, bark, branches, leaves) in the Iberian Peninsula (e.g., Montero et al 2005;Ruiz-Peinado et al 2012;Soares and Tomé 2012;Herrero et al 2014) and elsewhere (O'Grady et al 2006;Zewdie et al 2009). Antonio et al (2007) carried out a comprehensive study to estimate aboveground biomass components for that species in Portugal, including tree and stand explanatory variables.…”
Section: Introductionmentioning
confidence: 99%
“…The stands are normally exploited with three cutting cycles, and at the end of the commercial exploitation, the plantations must be re-established and the stumps removed prior to soil preparation (Barreiro and Tomé 2012;Soares and Tomé 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An example of ratio estimators in forestry is the estimate of biomass density with the aid of biomass expansion factor (BEF), where BEF is the ratio. Vegetation BEFs can be estimated either by mean-of-ratios [7][8][9] or by ratio-of-means [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%